2019
DOI: 10.3390/ijms20143571
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Origin and Evolution of the X1X2Y System in Two Closely-Related Oplegnathus Species (Oplegnathidae and Centrarchiformes)

Abstract: Oplegnathus fasciatus and O. punctatus (Teleostei: Centrarchiformes: Oplegnathidae), are commercially important rocky reef fishes, endemic to East Asia. Both species present an X1X2Y sex chromosome system. Here, we investigated the evolutionary forces behind the origin and differentiation of these sex chromosomes, with the aim to elucidate whether they had a single or convergent origin. To achieve this, conventional and molecular cytogenetic protocols, involving the mapping of repetitive DNA markers, comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 119 publications
(175 reference statements)
2
21
1
Order By: Relevance
“…In some organisms, differentiation of neo-Y or neo-W chromosomes starts early after their origin [82,[107][108][109][110][111]. Despite this, our data did not reveal any differentiation of Y chromosome of this species by the male-specific probe, which resembles the pattern found in neo-sex chromosomes in some other CGH-based studies [50,112,113]. Instead, the male probe differentiated a distal end of an acrocentric chromosome, which is involved in the formation of standard acrocentric bivalent during meiosis and the most likely explanation for this observation is the intraspecific variability in repetitive DNA content as discussed above in Section 4.1.…”
Section: Evolution Of Neo-sex Chromosome Systems In Spiderscontrasting
confidence: 61%
“…In some organisms, differentiation of neo-Y or neo-W chromosomes starts early after their origin [82,[107][108][109][110][111]. Despite this, our data did not reveal any differentiation of Y chromosome of this species by the male-specific probe, which resembles the pattern found in neo-sex chromosomes in some other CGH-based studies [50,112,113]. Instead, the male probe differentiated a distal end of an acrocentric chromosome, which is involved in the formation of standard acrocentric bivalent during meiosis and the most likely explanation for this observation is the intraspecific variability in repetitive DNA content as discussed above in Section 4.1.…”
Section: Evolution Of Neo-sex Chromosome Systems In Spiderscontrasting
confidence: 61%
“…Meaningly, a close association between microsatellites, rDNAs and multiple sex chromosomes has been reported for many fish taxa [ 55 , 56 , 57 , 58 , 59 ], which highlights the probable role of these sequences in the genesis of such systems. Despite our CGH data do not reveal any conspicuous Y-specific region, neither in both Y chromosomes of H. duriventris and H. villasboas , nor in the proto/neo-Y of H. rondoni , a slight binding preference for the male-derived probe occur at the pericentromeric region of all these chromosomes ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The situations described in Figure 6b,c show how translocations, fusions and rearrangements events among “A”, “B”, and “C” chromosomes could have originated a new chromosome called “F”. In the formation of sex chromosomes events such as fusions between sex chromosomes and autosome of the type Y-A has been described [13], or in the formation of (XX/XY 1 Y 2 ) multiple system in neo tropical fish [2], or in the X 1 X 2 Y sex system, which was formed through a centric fusion of ancestral Y chromosome with an autosome, creating a large neo-Y chromosome in the Oplegnathus genus [14]. In the situation described in Figure 6d only translocations and rearrangements are proposed to originate the “F” chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…This type of fusions has been observed at higher rates in fish and squamates reptiles than other sex chromosomes-autosomes fusions, being the XY lineages more frequently fused than ZW [13]. Hence, in two species of fishes of the Oplegnathus genus it was observed that multiple X 1 X 2 Y sex chromosomes were formed through a centric fusion of ancestral Y chromosome with an autosome, creating a large neo-Y chromosome [14]. The Neotropical fish H. malabaricus (Erythrinidae family) was described as having five karyomorphs, one of these, the (XX/XY 1 Y 2 ) multiple systems G, derived by tandem fusion events between the acrocentric proto-sex chromosome pair and the submetacentric autosome pair from ancestral karyotype, [2].…”
Section: Introductionmentioning
confidence: 99%